EVALUATION OF URIC ACID, CREATININE, AND ESTIMATED GLOMERULAR FILTRATION RATE IN ELDERLY AND ADOLESCENT POPULATIONS IN NNEWI METROPOLIS (Journal of Biomedical Investigation, 2024)
Background: Kidney efficiency declines with age due to cumulative cellular damage, while adolescence involves rapid physiological and hormonal changes that impact uric acid levels. Elevated uric acid is associated with gout, metabolic syndrome, and kidney diseases. Creatinine, a key marker of glomerular filtration, is influenced by muscle mass, while eGFR, a commonly used indicator of kidney function, naturally declines with age.Aim: This study compared the levels of uric acid, creatinine, and estimated glomerular filtration rate (eGFR) among elderly and adolescent populations in Nnewi, Anambra State, Nigeria.Materials and Methods: The study recruited 90 participants, comprising 45 adolescents (15–25 years) and 45 elderly individuals (60 years and above). Serum uric acid and creatinine levels were measured spectrophotometrically, and eGFR was calculated using the Modification of Diet in Renal Disease (MDRD) equation. Data were analyzed using independent t-tests and Pearson correlation coefficients at < 0.05 level of significance.Results: The results showed significant differences in uric acid, creatinine, and eGFR levels between adolescents and the elderly. The elderly had lower uric acid levels (264.19 ± 97.56 mg/dL) Vs adolescent (272.78±61.99mg/dL) higher creatinine levels (92.72 ± 18.37 µmol/L) Vs adolescent (73.57±15.19 µmol/L), and lower eGFR (68.99 ± 14.83 mL/min/1.73m²) compared to adolescents (111.00±17.00mL/min/1.73m²) (P < 0.05). Blood pressure and anthropometric measurements also differed, with the elderly showing higher blood pressure values. Correlation analysis highlighted significant links between uric acid levels and anthropometric indices, particularly in the elderly group.Conclusion: These results emphasize age related differences in renal function markers, with elderly individuals showing elevated creatinine levels and decreased eGFR, suggesting a decline in kidney function compared to adolescents.
Keywords: Kidney Function; Uric acid; Creatinine; Adolescent; eGFR